SIMULATION OF THE PROCESS OF SELECTION OF THE OPTIMUM TYPE OF ROLLING STOCK FOR TRANSPORTATION OF MEDICINES TO THE CONSUMER - Sayidkamolov Islomjon Rakhmatullo ugli; Nasirov Ilham Zakirovich (Scholar Express Journal, 2022)
The work was carried out modeling the process of choosing the optimal type of rolling stock for the transportation of medicines to the consumer. The optimal pair for transportation of the entire daily volume was chosen as a euro pallet with dimensions of 800x1200x145mm and a KamAZ-4308 vehicle with a static load capacity utilization factor of 1.023.
Keywords: rolling stock; pallet; container and packaging; medication